Statins and long-term risk of revision surgery after total hip arthroplasty in osteoarthritis: a multi-source data linkage study - D'Amuri, Andrea; Bordini, Barbara; Pagani, Mauro; Ciaffi, Jacopo; D'Agostino, Claudio; Di Martino, Alberto; Faldini, Cesare; Ursini, Francesco (Frontiers in Pharmacology, 2025)
BackgroundStatins, widely used lipid lowering drugs, have been associated with pleiotropic beneficial effects. Notably, studies conducted in vitro and in vivo suggest a link between statins and bone metabolism. Observational data in humans also hint at a decreased fracture rate among statin users. Revision of total hip arthroplasty (THA) is a serious and costly medical event. Whether statins might influence THA failure is not clear. Aim of the current study is to assess how the preoperative use of statins may influence the risk of THA revision in patients with hip osteoarthritis (OA).MethodsWe performed a retrospective analysis of patients who underwent THA for OA in the Italian RIPO registry of Emilia-Romagna. Electronic health records were scrutinized to gather information regarding comorbidities and statin prescriptions. We employed propensity score (PS) matching to pair 1:1 statin users (SU) with statin non-users (SNU), considering factors such as age, sex, and the duration of follow-up. Survival of THA was compared between the two groups; secondary analyses were performed to ascertain the role of mortality, sex, indication for statin treatment, and statin potency or lipophilicity.Results10,927 patients were classified as SU and PS-matched with SNU. SU showed a reduced risk of THA revision over a 15-year period (adjHR 0.76, 95% CI: 0.67–0.88; p < 0.001). Notably, this observation remained consistent regardless of the indication for statin therapy or the specific characteristics of the statin medications prescribed, and it was more pronounced among male patients (adjHR 0.64, 95% CI: 0.52–0.80, p < 0.001).ConclusionOur findings suggest that statin treatment is associated with a decreased risk of long-term THA revision in patients with OA, irrespective of the original indication for statin therapy.